HP‐SPC algorithm with dynamic partially connected structure for mmWave MIMO systems. Issue 7 (28th February 2022) - Du, Ruiyan; Liu, Huajing; Guan, Zhiqing; Liu, Fulai
Abstract: This article proposes a low complexity hybrid precoding algorithm for the switch network‐based dynamic partially connected (SPC) structure, that is, named as HP‐SPC algorithm. First, via a new defined effective optimal precoding matrix, the analog switch precoding matrix optimization problem is transformed into a sparse representation problem. Thus, invoking that the key characteristic of only one nonzero entry in each row of the analog dynamic switch precoding matrix, the analog dynamic switch precoding matrix can be accurately and effectively solved. Second, the digital precoding matrix optimization problem is modeled as a dictionary update problem by the defined effective optimal precoding matrix and the combining matrix. Further, the digital precoding matrix is easily optimized based on the defined effective optimal precoding matrix, since the measurement vectors are sparsely represented by a single dictionary atom. Third, the analog phase shifter precoding matrix is given by the phase rotation method. Finally, the precoding matrices are alternant updated until convergence, a near optimal solution of the precoding matrix is obtained. Compared with the previous works, the proposed HP‐SPC algorithm provides better hybrid precoding performance, for examples: (1) it avoids complexity computation such as matrix inversion and singular value decomposition, so that it presents a low computational complexity; (2) it has a favorable property of convergence since a stable point can be reached with about 10 loop iterations. Based on the simulation results, the effectiveness of HP‐SPC algorithm is further demonstrated. Abstract : We introduce a hybrid precoding algorithm to improve the spectral efficiency and reduce the computational complexity of switch network‐based dynamic partially connected for millimeter wave multiple‐input multiple‐output system. Invoking compressed sensing, the proposed algorithm alternately optimizes the precoding matrices and enjoys satisfactory computational complexity.